Austria - Wyld, James, 1790-1836 (artist):::Creator::::::::::::; Hewitt, N.R. (engraver):::Contributor:::::::::::: (Edinburgh; unJohn Thomson & Co.; United Kingdom)
Engraved map of Austria, including a small inset with a panoramic view of Vienna.